Noise pollution: it’s time to noise about - Chaudhary, Bhupendra; Chaudhary, Ansh (International Journal of Advances in Medicine, 2020)
Carrying the reputation of silent killer of 21st century, ‘Noise’ a modern day pollutant is defined as an unpleasant, disharmonic and undesired acoustic signal. World Health Organization (WHO) has estimated it dimensions and warned that 10% of the population is exposed to both short and long term health related issues due to noise. Whilst facing the conflict between development and human health, the noise favors the present day industrialization and urbanization. The harmful effect of noise may start from intrauterine life and continues till old age. Noise of more than 85-95dB affects both the fetus and neonates by damaging the cochlear hair cell and results in high frequency hearing loss. At times prematurity, low birth rate and birth defects are also associated with exposure to high dB noise.